Некоторые особенности динамических режимов электромеханической системы с асинхронным электроприводом - Герасимяк, Ростислав Павлович; Бабийчук, Ольга Борисовна; Субботин, Виктор Владимирович (НТУ "ХПИ", 2013)
A method of accounting for the influence of viscous friction in the deformation of the elastic connection of the electromechanical system with a two-mass mechanical part is proposed. Its role in reducing the rate of dynamism is illustrated. The opportunity of applying additional corrective feedback, which allows to significantly reduce the load in the kinematic gear mechanism is proved.
Keywords: двухмассовая механическая часть; зубчатые зацепления; момент инерции; коэффициент динамичности; диссипация; демпфирование